The road of lost innocence - Mam, Somaly (Spiegel & Grau, 2008)
"Originally published in France as Le silence de l'innocence by Editions Anne Carriere, Paris, in 2005"--T.p. verso.; Born in a village deep in the Cambodian forest, Somaly Mam was sold into sexual slavery by her grandfather when she was twelve years old. For the next decade she was shuttled through the brothels that make up the sprawling sex trade of Southeast Asia. Trapped in this dangerous and desperate world, she suffered the brutality and horrors of human trafficking - rape, torture, deprivation - until she managed to escape with the help of a French aid worker. Emboldened by her newfound freedom, education, and security, Somaly blossomed but remained haunted by the girls in the brothels she left behind." "The Road of Lost Innocence recounts the experiences of her early life and tells the story of her awakening as an activist and her harrowing and brave fight against the powerful and corrupt forces that steal the lives of these girls